Drug therapy of autonomic dysfunction in children - A.E. Abaturov; T.P. Borisova; A.A. Nikulina (Zaslavsky O.Yu., 2020)
The literature review gives general ideas about disorders of the autonomic nervous system, or autonomic dysfunction, in childhood. Autonomic dysfunction syndrome is one of the most common pathologies among the child population, which occurs in every third child, and in 17-20 % of children over the course of age can become the basis for the development of arterial hypertension, coronary heart disease, bronchial asthma, and frequent respiratory infections. Late diagnosis and inadequate treatment of autonomic dysfunction can lead to a significant decrease in the quality of life and the development of neuropsychiatric and somatic diseases. Treatment of autonomic dysfunction syndrome requires an integrated and individual approach in each case. The use of herbal preparations is one of the effective and safe methods of drug treatment for autonomic dysfunction in children and adolescents. Many clinical trials using a phytopreparation that contains taurine, a thick extract of motherwort (Leonurus cardiaca), a thick extract of hawthorn fruit (Crataegus oxyacantha L.) for the treatment of autonomic dysfunction in children have shown a sufficient efficacy and safety of its use. The effect of therapy for autonomic dysfunction in children with the drug, which includes taurine, a thick extract of motherwort (Leonurus cardiaca), a thick extract of hawthorn fruit (Crataegus oxyacantha L.), on the state of the cardiovascular system is characterized by: normalization of heart rate, systolic, diastolic and average blood pressure, normalization of the circadian rhythm (an increase in the number of children with a normal circadian type of blood pressure - dippers), a decrease in the risk of non-paroxysmal tachycardia, restoration of the pacemaker's excitability, reduction of the manifestation of the syndrome of early ventricular repolarization. Thus, a phytopreparation that contains taurine, a thick motherwort extract (Leonurus cardiaca), a thick extract of hawthorn fruit (Crataegus oxyacantha L.) can be considered the drug of primary choice in the treatment of autonomic dysfunction syndrome, which is accompanied by a tendency to develop hypertension.